Pengaruh Literasi Keuangan Keluarga Katolik Terhadap Kolekte Paroki Santo Joseph Passo - Balia, Selvia (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2025)
One type of parish income is the collection given by Catholics every Sunday. The collection is usually allocated for worship activities, sustenance, and services to the poor. This paper is sociological research with a quantitative approach. It aims to analyse the financial literacy of Catholic families in the Sacred Heart and the Mother of the Sacred Heart of Jesus Associations, and its influence on collections at the Saint Joseph Passo Parish. The main question addressed is: “To what extent does the financial literacy of Catholic families influence collections every Sunday at the Saint Josep Passo Parish?” The results of the questionnaire test showed that the parishioners believe that the blessings they receive must be given to God. Therefore, they consciously and willingly give collections at the Eucharist every Sunday. However, the research test proved that the financial literacy of Catholic families did not have a significant effect on the collections of parishes. This article proposes that financial literacy needs to be given to every Catholic family in the Parish of Saint Joseph Passo so that they are able to manage family finances according to household needs, and give collections at the Eucharist Celebration every Sunday.